Influence of morphological characteristics of stem and panicle length on wintering oat lodging resistance - M. V. Kuzenko; V. I. Kuzenko (Новые технологии, 2020)
The article presents the results of investigating morphological parameters of a stem and a panicle of wintering oat varieties and hybrid populations of the nursery of competitive variety trial and Avena fatua (L.) field weed species. The research has been carried out in order to identify differences in morphological characteristics of cultivated and weed-field types of oats, as well as to search for economically useful characteristics for practical use in breeding. The research focuses on lodging resistance as one of the significant economically valuable signs of increasing wintering oat productivity. The studied samples have been analyzed according to plant height, number and length of internodes, and panicle length. The role of the length of internodes and panicles in the formation of the height of both species has been determined. Differences in the length of internodes have been revealed when compared with the standard and Avena fatua (L.). The relationship between internodes and panicles with height has been shown, as well as the dependence of the developed length of each internode between the nodes of the plant itself. The performed correlation analysis has revealed the presence of a high positive relationship between the height of wintering oat plants and the length of the fifth internode (0,61) and panicle (0,91). The presence of these connections indicates the need for forms of oats with a short fifth internode and a panicle in order to increase the resistance to lodging in crosses. The use of the results of morphological analysis complements the visual assessment of lodging resistance, makes it possible to characterize the parental forms used in the hybridization process, and to promote the accelerated development of varieties resistant to stem lodging.